2020
DOI: 10.1007/s10346-020-01531-2
|View full text |Cite
|
Sign up to set email alerts
|

Discrete element analysis of dry granular flow impact on slit dams

Abstract: Slit dam is an open-check barrier structure widely used in mountainous regions to resist the destructive impacts of granular flows. To examine the dynamics of granular flow impact on slit dams, a numerical study by discrete element method (DEM) is presented in this article. The study considers dry granular materials flowing down a flume channel and interacts with slit dams installed at the lower section of the flume. The particle shape is explicitly considered by particle clumps of various aspect ratios. The s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 34 publications
(13 citation statements)
references
References 35 publications
1
12
0
Order By: Relevance
“…r / F v gh = , where v is the granular flow velocity and h is the flow depth, which is closely related to the impact behavior of granular flow. In the field observation, the Froude number normally ranges from 0.5 to 7.6 (Gong et al, 2021). The Froude number of granular flow ranged from 2.9 to 5.3 in this study.…”
Section: Model Size Effectmentioning
confidence: 58%
“…r / F v gh = , where v is the granular flow velocity and h is the flow depth, which is closely related to the impact behavior of granular flow. In the field observation, the Froude number normally ranges from 0.5 to 7.6 (Gong et al, 2021). The Froude number of granular flow ranged from 2.9 to 5.3 in this study.…”
Section: Model Size Effectmentioning
confidence: 58%
“…Texier et al [8][9][10][11][12][13] investigated the effects of natural angle of repose, particle gradation distribution, particle size, water content, particle roundness, particle gradation and other factors on bulk slope stability. Fan Limin et al 14 obtained through theoretical analysis that the main factors affecting the runoff flow rate at the surface of the slope and the seepage flow rate inside the slope body are slope gradient, runoff water depth, porosity and permeability of the bulk granular body of the slope, and the flow rate increases with its increase Marchelli, M. et al 9,10,[15][16][17][18][19][20][21] conducted a study on the preventive and curative measures against disasters of the bulk granular slopesretaining walls, slit dams, and detention barriers. Li, X. Y.et al 22 investigated the effect of earthquakes on the stacking morphology of bulk slopes and found that the direction of vibration had a significant effect on the shape of the stacks, and the values of the stroke were larger when the direction of vibration was horizontal than when the direction of vibration was vertical, whereas the values of the stacking width and thickness were smaller than when the direction of vibration was vertical.…”
Section: Introductionmentioning
confidence: 99%
“…Some studies compared velocities at the tip of flowing granular materials [5,6]; however, their validity was often confirmed by only the final deposition shape [7,8]. In these studies, the granular avalanche experiments, which were performed for comparing the results with those of numerical simulations, considered constant slope angles and slope heights.…”
Section: Introductionmentioning
confidence: 99%